Assessment of diet quality among married couples in a selected urban area in Selangor - Asma’ A,; Nawalyah AG,; Rokiah MY,; Mohd Nasir MT, (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2010)
The aim of this study was to assess the overall diet quality of husbands and wives in a selected urban area in Selangor. Methodology : This cross-sectional study was carried out in Bandar Baru Bangi, Selangor among 150 married couples aged 20 and above, who voluntarily agreed to participate and were not practicing any special diet. Data were collected using a 2-day 24-Hour Dietary Recall and a Food Frequency Questionnaire (FFQ) to evaluate the quality of diet among husbands and wives using the Diet Quality Index Revised (DQI-R). Result : Majority of husbands and wives in this study were in the middle-age group, had received tertiary education, had household monthly income of more than RM3, 500 and encompass household size of 3 to 5 persons. The mean DQI-R score for husbands (mean age= 43.33 + 11.16 years) and wives (mean age= 41.28 + 10.93 years) were 67.8 + 9.1 and 64.4 + 9.3 respectively and there was a significant different in scores between the husbands and wives (p < 0.001). In general, the diet quality of this study population was not satisfactory and that the diet quality of husbands was better compared to their wives. Conclusion : This study gives an insight picture of husbands and wives’ quality of diet. It can be used as a guideline to improve health intervention programs in the future.